Fluorescence quenching by high-power LEDs for highly sensitive fluorescence in situ hybridization - Tsuneoka, Yousuke; Atsumi, Yusuke; Makanae, Aki; Yashiro, Mitsuru; Funato, Hiromasa (Frontiers in Molecular Neuroscience, 2022)
Recent technical advances have made fluorescent in situ hybridization (ISH) a pivotal method to analyze neural tissue. In a highly sensitive ISH, it is important to reduce tissue autofluorescence. We developed a photobleaching device using a light-emitting diode (LED) illuminator to quench autofluorescence in neural tissue. This device was equipped with 12 high-power LEDs (30 W per single LED) and an evaporative cooling system, and these features achieved highly efficient bleaching of autofluorescence and minimized tissue damage. Even after 60 min of photobleaching with evaporative cooling, the temperature gain of the tissue slide was suppressed almost completely. The autofluorescence of lipofuscin-like granules completely disappeared after 60 min of photobleaching, as did other background autofluorescence observed in the mouse cortex and hippocampus. In combination with the recently developed fluorescent ISH method using the hybridization chain reaction (HCR), high signal/noise ratio imaging was archived without reduction of ISH sensitivity to visualize rare mRNA at single copy resolution by quenching autofluorescence. Photobleaching by the LED illuminator was also effective in quenching the fluorescent staining of ISH-HCR. We performed multiround ISH by repeating the cycle of HCR staining, confocal imaging, and photobleaching. In addition to the two-round ISH, fluorescent immunohistochemistry or fluorescent Nissl staining was conducted on the same tissue. This LED illuminator provides a quick and simple way to reduce autofluorescence and quench fluorescent dyes for multiround ISH with minimum tissue degradation.